Angelica gigas ameliorate depression-like symptoms in rats following chronic corticosterone injection - Lee, Bombi (BMC Complement Altern Med, 2015)
BACKGROUND: Repeated injection of corticosterone (CORT) induces dysregulation in the hypothalamic-pituitary-adrenal (HPA) axis, resulting in depression. We examined the effects of Angelica gigas extract (AGN) treatment in a rat model of depressive and anxiety-like behaviors, induced by chronic CORT exposure. METHODS: Male rats received 10, 20, or 50 mg/kg AGN (i.p.) 30 min prior to a daily injection of CORT for 21 consecutive days. Activation of the HPA axis in response to the repeated CORT injections was confirmed by measuring serum levels of CORT and the expression of corticotropin-releasing factor in the hypothalamus. RESULTS: Daily AGN administration significantly reversed the depression and anxiety-like behavioral abnormalities. It also blocked increases in tyrosine hydroxylase expression in the locus coeruleus, and suppressed the decreased expression levels of brain-derived neurotrophic factor (BDNF) and its receptor TrkB mRNAs in the hippocampus. CONCLUSIONS: These findings indicate that administration of AGN prior to high-dose exogenous CORT significantly improved helpless behaviors, possibly by modulating the central noradrenergic system and regulation of BDNF expression in rats. Thus, AGN may be a useful agent for the treatment or alleviation of psychiatric disorders associated with depression and anxiety disorders.